Duplex ultrasound: A diagnostic tool for carotid stenosis management in type 2 diabetes mellitus - Yogan Kisten; Pravesen Govender; Nadraj G. Naidoo; Dhiro Gihwala; Ferial Isaacs (AOSIS, 2013)
Background: Diabetic patients are at increased risk of developing cardiac events and stroke, and prevention of diabetes mellitus is therefore desirable. Marked geographical and ethnic variation in the prevalence of diabetes caused by urbanisation, demographic and epidemiological transitions has rendered this one of the major non-communicable diseases in South Africa. Duplex ultrasound (DUS) plays an important role in primary health care in early detection of carotid atherosclerotic disease and the degree of carotid stenosis present. It is a reliable, cost-effective and non-invasive diagnostic tool. The purpose of this study was to determine the role of ultrasound in carotid stenosis management in type 2 diabetes mellitus (T2DM). Objectives: To determine the prevalence of carotid stenosis in a selected T2DM population using DUS and to correlate these findings with other predisposing atherosclerotic risk factors. Methods: The study setting was at an academic hospital in the Western Cape using carotid DUS reports of 103 diabetic subjects ≥ 35 years old. Predisposing risk factors were correlated with degree of carotid stenosis present. Data were analysed using the Fischer exact test, Chisquare and Student t-test. Results: Carotid DUS reports of 63 out of 103 T2DM patients revealed no evidence of a carotid stenosis, thereby lowering the risk profile. Forty patients were identified as having carotidstenosis; 22 symptomatic patients had a > 70% carotid stenosis which warranted surgicalintervention. A greater prevalence of stenosis in the Caucasian group, in both the male (p =0.0411) and female (p = 0.0458) cohorts, was noted. The overall trend suggested a relationship between T2DM and lifestyle, and a statistically significant relationship (p = 0.0063) between smoking and carotid stenosis was observed. Conclusion: T2DM and predisposing atherosclerotic risk factors significantly increased thepossibility of carotid stenosis development.